Direct interaction between EgFABP1, a fatty acid binding protein from Echinococcus granulosus, and phospholipid membranes. - Jorge L Porfido; Gabriela Alvite; Valeria Silva; Malcolm W Kennedy; Adriana Esteves; Betina Corsico (PLoS Neglected Tropical Diseases, 2012)
Background Growth and maintenance of hydatid cysts produced by Echinococcus granulosus have a high requirement for host lipids for biosynthetic processes, membrane building and possibly cellular and developmental signalling. This requires a high degree of lipid trafficking facilitated by lipid transporter proteins. Members of the fatty acid binding protein (FABP) family have been identified in Echinococcus granulosus, one of which, EgFABP1 is expressed at the tegumental level in the protoscoleces, but it has also been described in both hydatid cyst fluid and secretions of protoscoleces. In spite of a considerable amount of structural and biophysical information on the FABPs in general, their specific functions remain mysterious. Methodology/principal findings We have investigated the way in which EgFABP1 may interact with membranes using a variety of fluorescence-based techniques and artificial small unilamellar vesicles. We first found that bacterial recombinant EgFABP1 is loaded with fatty acids from the synthesising bacteria, and that fatty acid binding increases its resistance to proteinases, possibly due to subtle conformational changes induced on EgFABP1. By manipulating the composition of lipid vesicles and the ionic environment, we found that EgFABP1 interacts with membranes in a direct contact, collisional, manner to exchange ligand, involving both ionic and hydrophobic interactions. Moreover, we observed that the protein can compete with cytochrome c for association with the surface of small unilamellar vesicles (SUVs). Conclusions/significance This work constitutes a first approach to the understanding of protein-membrane interactions of EgFABP1. The results suggest that this protein may be actively involved in the exchange and transport of fatty acids between different membranes and cellular compartments within the parasite.